Impact of particle concentration and out-of-range sizes on the measurements of the LISST. (11th April 2018) - Zhao, Lin; Boufadel, Michel C; King, Thomas; Robinson, Brian; Conmy, Robyn; Lee, Kenneth
Abstract: The instrument LISST (laser in situ scattering and transmissiometry) has been widely used for measuring the size of oil droplets in relation to oil spills and sediment particles. Major concerns associated with using the instrument include the impact of high concentrations and/or out-of-range particle (droplet) sizes on the LISST reading. These were evaluated experimentally in this study using monosized microsphere particles. The key findings include: (1) When high particle concentration reduced the optical transmission (OT) to below 30%, the measured peak value tended to underestimate the true peak value, and the accuracy of the LISST decreased by ~8% to ~28%. The maximum concentration to reach the 30% OT was about 50% of the theoretical values, suggesting a lower concentration level should be considered during the instrument deployment. (2) The out-of-range sizes of particles affected the LISST measurements when the sizes were close to the LISST measurement range. Fine below-range sizes primarily affected the data in the lowest two bins of the LISST with  >75% of the volume at the smallest bin. Large out-of-range particles affected the sizes of the largest 8–10 bins only when very high concentration was present. The out-of-range particles slightly changed the size distribution of the in-range particles, but their concentration was conserved. An approach to interpret and quantify the effects of the out-of-range particles on the LISST measurement was proposed.